THE PRINCIPLES OF THE NATIONAL POLICE OF UKRAINE - Semerey, Bohdan (SUPREMANCE OF LAW, 2016)
Reorganization of the internal Affairs bodies implies a profound transformation concerning the essence and activities of the police, the updating of the content of her work. The cornerstone erected by the rights and freedoms of citizens. Their protection and respect should be the main goal of the police is the population to assess the reliability and efficiency of its activities on the essence and principles of the National police of Ukraine.
Keywords: internal Affairs bodies; the media; publicity; police; transparency; principles; essence of the principles; the national police; administrative law; legislation